(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
Increasing employee engagement through organizational culture has numerous advantages for the organization. When employees are involved in the process of making decisions, they are more cooperative in accepting them and more committed, leading to increased performance. This paper aims to evaluate the impact of participatory management on organizational culture and performance. According to the available literature and research background, three hypotheses are formed and tested. A standard questionnaire is used as the data collection tool, distributed among employees of District 6 of Isfahan Municipality. The collected data are analyzed using SPSS V.18.0 and AMOS V.20.0 software packages. The results show that participatory management has both direct and indirect, through organizational culture, impacts on organizational performance.